The Design Of Tasks In "Bahasa Inggris For Ninth GradeStudents Of Junior High School" English Workbook In Candlin's Perspective (1987) - Susilasari, Indah; , Prof. Dr. Endang Fauziati, M. Hum; , Nur Hidayat, M.Pd (2014)
This article represents the design of tasks presented in an English workbook Bahasa Inggris viewed from the theory of characteristic of good task proposed by Candlin. The objectives of the research are to describe how the tasks provided in the book are designed based on 8 criteria proposed by Candlin. The writer employs descriptive analysis. The data of the research are the tasks presented in the workbook Bahasa Inggris. The data source is "Bahasa Inggris" workbook, written by Teacher Association in Wonogiri Regency. Having analyzed the textbook, the researcher concludes that: the tasks designed based on 8 criteria proposed by Candlin are include tasks model such as word matching, completion, translation, oral production by using picture, story telling task, oral interview, constructing sentence, comprehension task involving pairs and groups work, role play, constructing sentence, guessing, picture-sentence matching, sentence matching, reading aloud, dialog composition and jumbles task and by the percentage that is shown in research finding, the result of the percentage shows that 87,5 % task in the workbook appropriate with the criteria of good task suggested by Candlin. By using criterion of evaluation proposed by Nurgiyantoro, it can be concluded that the task provided in the workbook are categorized as very good task.